The Problems of Productive Waqf Management in Indonesia using ISM Delphi - Ulfa, Nur Nazima (SMART Insight, 2023)
Waqf has a contribution to the country's economic development, if the waqf land is managed productively it will become a very large asset for the people and can be used for public welfare. However, at present the potential for waqf has not been used optimally in Indonesia. There are many factors that cause suboptimal management of waqf, therefore the author tries to analyze the management of productive waqf in Indonesia seen from 2 elements: problem elements, and institutional/stakeholder elements. The method used is the Interpretive Structural Modeling (ISM) method and the Delphi method. The results of this study of elements of problems which are the highest ranks are the less of educational or public understanding of waqf, less of public trust in Nazhir institutions and weak political will of authority holders. Then the highest rank of the related institutional elements are BWI, Ministry of Religious Affair, and DSN-MUI.